2023
DOI: 10.2147/jaa.s392733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Management, and Risk Factors of Asthma Among School-Age Children in Yogyakarta, Indonesia

Abstract: Childhood asthma in developing countries has been increasing, but underdiagnosed and undertreated. We reported prevalence, management, and risk factors of asthma among school-age children in Yogyakarta, Indonesia. Patients and Methods: We recruited children aged 6-7 years and 13-14 years attending schools in all districts in Yogyakarta, Indonesia. The schools were randomly selected via cluster random sampling. We used the Indonesian version of the Global Asthma Network (GAN) questionnaire, and the methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
2
13
0
1
Order By: Relevance
“…We have read a paper by Rina Triasih et al on Prevalence, Management, and Risk Factors of Asthma Among School-Age Children in Yogyakarta, Indonesia. 1 We congratulate the authors for their invaluable findings in the world of health which provide information regarding asthma, especially in children whose cases have not gone away. We would like to share our views on this study as well as provide input that can build on and develop this research if it is to be continued in the future by other researchers who also want to conduct studies on the prevalence of asthma, especially in school-age children.…”
Section: Dear Editormentioning
confidence: 99%
“…We have read a paper by Rina Triasih et al on Prevalence, Management, and Risk Factors of Asthma Among School-Age Children in Yogyakarta, Indonesia. 1 We congratulate the authors for their invaluable findings in the world of health which provide information regarding asthma, especially in children whose cases have not gone away. We would like to share our views on this study as well as provide input that can build on and develop this research if it is to be continued in the future by other researchers who also want to conduct studies on the prevalence of asthma, especially in school-age children.…”
Section: Dear Editormentioning
confidence: 99%
“…The meta‐analysis by Sio et al 27 demonstrated that PM 10 increased the overall risk of asthma by 1.22‐fold ( n = 8 studies) in Asian countries. In India and Indonesia, frequent passage of trucks near residential houses has been associated with a 1.7 times higher risk of wheezing in children 39,40 …”
Section: Risk Factors Of Asthmamentioning
confidence: 99%
“…On the other hand, poor diet such as fast‐food consumption was associated with increased risk of current wheeze, while fruit intake of more than twice a week was protective 39,40 . Higher intake of polyunsaturated fatty acids may provoke Th2‐related asthma by increasing the production pro‐inflammatory mediators 45 .…”
Section: Risk Factors Of Asthmamentioning
confidence: 99%
See 2 more Smart Citations